A Modular Architecture for the Design of Condition Monitoring Processes - Fleischmann, Hans; Kohl, Johannes; Franke, Jörg (Procedia CIRP, 2016)
The increasing complexity of production plants in the context of Industry 4.0 poses new challenges with regards to technical maintenance and process control. In this context, Cyber-Physical Systems (CPS) for intelligent condition monitoring enable fault-tolerant, predictable production systems. Unfortunately, CPS and Condition Monitoring System development is challenging due to the distribution of computational tasks among heterogeneous industrial IT-architectures. It is usually started from scratch, which is time-consuming and error-prone. In times of CPS the employee as maintenance worker, who ensures the availability of production machinery, is still important. In order to address these challenges, this publication we propose a modular architecture for Socio-CPS-based condition and process monitoring as well as fault diagnostics.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Condition Monitoring Systems; Industry 4.0; Socio-Cyber-Physical Systems; Technical Diagnosis